The misprescribing of Z-drugs for insomnia - David O’Regan (Advances in Clinical Neuroscience & Rehabilitation, 2019)
Scarcely a day goes by without sleep being in the news. One long-running strand concerns media coverage of sleep medicines, particularly the Z-drugs (i.e. Zopiclone and Zolpidem), which have tended over time to receive a bad press. Rising prescription numbers, escalating costs to the NHS, and raised mortality risks all hint at an epidemic of “misprescribing”, creating new anxieties for our patients with insomnia to keep them awake at night. Conversely though, there is a paucity of information available on what constitutes “good” Z-drug prescribing. What is more, various guidelines tend to imply that the right answer exists, rather than recognising the complex trade-offs that often have to be made. One model of good prescribing brings together the traditional balance of benefits and risks, with the need to reduce costs, and the right of patients to make treatment choices1 (see Figure 1). Using this model, I explore how to avoid misprescribing Z-drugs.